2008
DOI: 10.1159/000114643
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Expression in the Sheep Brain

Abstract: Accumulating evidence in rodents suggests that a prolactin locally synthesized and released within the brain can act together with that taken up from the circulation to modulate neuroendocrine responses. The present study was designed to identify the regional patterns of prolactin expression in the adult and developing sheep brain. Specifically, we tested the hypothesis that prolactin is expressed in regions of the adult and fetal sheep brain that are critical in the development of neuroendocrine homeostatic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 88 publications
0
19
0
2
Order By: Relevance
“…PRL regulates its own secretion at the level of the hypothalamus, where the wide influence of PRL on brain functions is thought to be required for neurobiological adaptations during preparation for pregnancy and lactation . The detection of pPRL mRNA expression in the brain and hypothalamus was expected given data from rats , sheep (Roselli et al 2008), and mice (Chen et al 2004). Combined, these data suggest that PRL may mediate some actions in the brain by acting as a neuropeptide as well as a neuroendocrine hormone .…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…PRL regulates its own secretion at the level of the hypothalamus, where the wide influence of PRL on brain functions is thought to be required for neurobiological adaptations during preparation for pregnancy and lactation . The detection of pPRL mRNA expression in the brain and hypothalamus was expected given data from rats , sheep (Roselli et al 2008), and mice (Chen et al 2004). Combined, these data suggest that PRL may mediate some actions in the brain by acting as a neuropeptide as well as a neuroendocrine hormone .…”
Section: Discussionmentioning
confidence: 67%
“…Extrapituitary sources of PRL in humans, rodents, and ruminants include uterine and brain tissues, lacrimal, sweat, and adrenal glands, immune and mammary epithelial cells, skin fibroblasts, kidney, and the ovary (Fields et al 1993, Doppler 1994, Ben-Jonathan et al 1996, Prigent-Tessier et al 1999, Sakai et al 1999, Tao et al 2004, Kobayashi et al 2007, Roselli et al 2008. Interestingly, PRL appears to not be expressed in the rat liver (Kurtz et al 1993), a tissue rich in PRLR (Bole-Feysot et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The original observation of IR-PRL in the hypothalamus of rats 33 was supported by several groups, [34][35][36][37][38][39] although one study showed cross-reactivity of PRL antiserum with pro-opiomelanocortin, 40 which might account for some of the observations. Subsequently, PRL mRNA has been detected in brain tissue by reverse transcriptase-polymerase chain reaction (RT-PCR) [41][42][43][44][45] but, apart from one study identifying expression in fetal sheep brains, 46 it has not been localised by in situ hybridisation. 41,42 One explanation might be that these studies actually detected pituitary PRL after transport from the periphery, although, at least in one of these studies, 36 PRL-like immunoreactivity was not eliminated by hypophysectomy, suggesting that it was unlikely to be of pituitary origin.…”
Section: Source S Of Prol Ac Tin: Is There Neur Al Produc Tion Of Pmentioning
confidence: 99%
“…2002), suggesting an activated state of the brain prolactin system during the peripartum period. Recently, Roselli et al. (2008) have shown that in sheep, prolactin is synthesized within the hypothalamus‐preoptic area and amygdala, where they documented the presence of both prolactin protein and mRNA expression.…”
Section: Introductionmentioning
confidence: 99%